Pembinaan Akhlak Santriawati Di Pesantren Modern Ar-Raudhatul Hasanah Paya Bundung Simpang Selayan Kecamatan Medan Tuntungan - Ramadhani, Utari (UIN Sumatera Utara, 2024)
The orientation of education is the formation of noble character in accordance with the teachings brought by the Prophet Muhammad SAW, he placed the perfection of morals as the main mission of the message of Islam. The purpose of this study is to determine moral development, morality is a trait embedded in the soul that encourages a person to perform actions without the need for thought and consideration. The morality is born from a habit and is ingrained into a personality. Therefore, it can be understood that morality can have a good and bad impact on oneself and the environment. Morals are the focus of all divine religions, including Islam. Morals is a theme that has always been of great concern to Islamic scholars and will continue to be so throughout the ages. After doing the research, this research focuses on showing that the coaching process carried out by the Ar-Raudhatul Hasanah Islamic Islamic Boarding School Paya Bundung Simpang Selayang, Medan Tuntungan District, is widely supported by daily activities that are implemented to be obeyed by all students and female students, the way the ustadz/ustadzah educates students in learning process, and extracurricular activities. Researchers also found supporting and inhibiting factors during the coaching process. The method used in this research is qualitative with research results in the form of descriptive data obtained from various sources using a qualitative descriptive approach.